(untitled) (Communications in Mathematical Research, 2020)
Framed links in thickened torus are studied. We define the mod 2 Kauffman bracket skein module of thickened torus and give an expression of a framed link in this module. From this expression we propose a new ambient isotopic invariant of framed links.